ANALISIS FAKTOR PENYEBAB KESULITAN MEMBACA PADA PESERTA DIDIK KELAS RENDAH - Sudharsono, Muhammad; Azzahra, Siti Salma; Khasanah, Febi Nurul; Yanti, Sur; Kaddafi, Torik (Jurnal Riset Pendidikan Dasar (JRPD), 2025)
Abstract. Understanding the factors of reading difficulties is important to design the right strategies in supporting students' reading development. The success and accuracy of reading is the first phase of the stage that has a great influence on the next reading ability achievement. Reading difficulties are an obstacle that is often experienced by students at the basic education level, and can affect their academic development. The study was conducted to analyze what factors play a role in reading difficulties in elementary school students. The research was conducted with a qualitative approach with literature study methods. The results of this study show that the influence that causes reading difficulties in lower grade students is divided into two factors, namely internal factors such as cognitive ability and language impairment, as well as external factors such as students who lack support from their parents and limited learning facilities. This research is expected to provide knowledge for educators and related parties in designing better interventions to be able to develop students' reading skills. Keywords: Causal Factors, Reading Difficulties, Lower Grades, Elementary School Abstrak. Memahami faktor-faktor kesulitan membaca penting untuk merancang strategi yang tepat dalam mendukung perkembangan membaca siswa. Keberhasilan serta ketepatan membaca merupakan fase tahap pertama yang berpengaruuh besar pada kamjuan kemampuan membaca berikutnya. Kesulitan membaca merupakan kendala yang sering dijalani oleh peserta didik di jenjang pendidikan dasar, dan dapat memperngaruhi perkembangan akademik mereka. Penelitian dilakukan untuk menganalisis faktor apa saja yang berperan terhadap kesulitan membaca pada peserta didik kelas rendah sekolah dasar. Penelitian dilakukan dengan pendekatann kualitatif dengan metodi sstudi literatur. Hasil dari penelitian ini menunjukkan bahwa pengaruh yang menyebabkan kesulitan membaca pada siswa kelas rendah dibagi menjadi dua faktor, yaitu faktoor internal seperti kemampuan kognitif dan gangguan bahasa, serta faktor eksternal seperti contoh siswa kurang mendapatkan dukungan dari kudua orang tuanya dan keterbatasan fasilitas belajar. Penelitian ini di harapkan bisa menyediakan pengetahuan bagi pendidik dan pihak terkait dalam merancang intervensi yang lebih baik untuk dapat mengembangkan kemampuas membaca para siswa. Kata kunci: Faktor penyebab, Kesulitan Membaca, Kelas Rendah Sekolah Dasar.